Acting Rationally Without Really Thinking: The Logic of Rational Intuitionism for International Relations Theory1. Issue 3 (14th July 2015) - Holmes, Marcus; Traven, David
<x xml:space="preserve">Abstract</x> International Relations (IR) theorists have traditionally viewed rationality and consciousness as defining features of human behavior. But recently this approach has come under fire from several angles. Not only do many psychologists now consider rationality to be dependent on emotions, recent developments in the logics of action debate in IR theory explicitly argue for de‐emphasizing the role of consciousness and rationality in theorizing agency. In an effort to put rationality back into its proper place, we critique two recent contributions to the logics of action debate: practice theory and the logic of habit. Both logics of action are useful in many respects, but we argue that they rest on a view of individual agency that is too structural and insufficiently cognitive to fully understand how individuals make decisions in international politics. We do not doubt that unconscious reflexes often control individual decisions, but we maintain that cognitive control and deliberation play a much larger role in constructing these reflexes than practice theory and the logic of habit recognize. We sketch a rational intuitionist logic of action for IR theory. We argue that intuitions constitute the most useful way to theorize the unconscious determinants of individual action and that although intuitions control how people behave in particular circumstances, they are subject to rational recalibration through internal and intersubjective reasoning.